Membrane filter enumeration method for Clostridium perfringens. - Bisson, J W (1979)
A membrane filter procedure has been developed for the rapid quantitation of C. perfringens in the aquatic environment. Background growth is inhibited by the use of D-cycloserine, polymyxin B sulfate, and incubation at 45 degrees C. Differential characteristics include the fermentation of sucrose, production of acid phosphatase, and the absence of beta-D-glucosidase activity. The medium is prepared as follows (in grams per 100 ml of distilled water): tryptose, 3.0; yeast extract, 2.0; sucrose, 0.5; L-cysteine, 0.1; MgSO4. 7H2O, 0.01; bromocresol purple, 0.004; and agar, 1.5. The ingredients are dissolved, and the pH is adjusted to 7.6. After autoclaving at 121 degrees C for 15 min, the medium is allowed to cool at 50 degrees C, and the following are added per 100 ml: D-cycloserine, 40 mg; polymyxin B sulfate, 2.5 mg; indoxyl-beta-D-glucoside, 60 mg; 2.0 ml of a filter-sterilized 0.5% phenolpthalein diphosphate solution; and 0.2 ml of a filter-sterilized 4.5% FeCl3.6H2O solution. Enumeration of C. perfringens in a water sample is completed within 18 to 24 h. The verification of typical colonies was 93%. The average recovery from peptone-water spore suspensions of five strains was 79%, and that from filter-sterilized seawater suspensions was 90%. The precision of the method was approximately equal to that expected from random error alone. Confirmed recoveries of C. perfringens from water and sewage samples generally were greater than those by the Bonde pour tube method.